The effect of cookies moerhi on body weight and macronutrient intake in undernourished adolescent girls - Septiana, Dian; Nuhriawangsa, Adi Magna Patriadi; Rahardjo, Setyo Sri (Jurnal Gizi dan Dietetik Indonesia (Indonesian Journal of Nutrition and Dietetics), 2025)
ABSTRAKLatar Belakang: Gizi kurang merupakan salah satu permasalahan gizi yang sering menyerang remaja, khususnya remaja putri. Hal ini disebabkan oleh kurangnya konsumsi energi dan zat gizi dalam memenuhi kebutuhan tubuh. Salah satu strategi mengatasi gizi kurang adalah pemenuhan asupan gizi dengan memberikan suplementasi gizi berupa makanan tambahan yang digemari, misalnya cookies. Cookies Moerhi merupakan cookies yang dibuat dengan tepung ubi jalar putih (Ipomoea batatas L.) dan tepung tempe sebagai pengganti sebagian tepung terigu.Tujuan: Tujuan penelitian ini adalah untuk mengetahui pengaruh Cookies Moerhi terhadap berat badan dan asupan zat gizi makro pada remaja putri gizi kurang.Metode: Desain penelitian quasi experiment dengan pre-test and post-test with control group design. Penelitian dilaksanakan pada bulan Mei-Juni 2024, sampel berjumlah 33 orang yang terbagi menjadi 3 kelompok perlakuan yaitu: 1) kelompok kontrol diberi cookies kontrol dan edukasi gizi; 2) kelompok intervensi 1 diberi Cookies Moerhi formula 1 (20% tepung ubi jalar putih, 10% tepung tempe) dan edukasi gizi; 3) kelompok intervensi 2 diberi Cookies Moerhi formula 2 (10% tepung ubi jalar putih, 20% tepung tempe). Hasil: Hasil penelitian menunjukkan bahwa pemberian Cookies Moerhi formula 1 dan edukasi gizi selama 21 hari dapat meningkatkan rerata berat badan (p=0,009), asupan energi (p=0,007), protein (p=0,014) dan lemak (p=0,003), sedangkan Cookies Moerhi formula 2 dapat meningkatkan rerata asupan lemak (p=0,033). Cookies kontrol dapat meningkatkan rerata berat badan (p=0,006) dan asupan energi (p=0,030).Kesimpulan: Pemberian Cookies Moerhi formula 1 dan edukasi gizi menunjukkan hasil yang lebih baik karena dapat meningkatkan berat badan, asupan energi, asupan protein dan asupan lemak pada remaja putri gizi kurang. Kata Kunci: asupan zat gizi makro; berat badan; cookies; gizi kurang; remaja  ABSTRACTBackground: Undernourished is one of the nutritional problems that often attacks adolescents, especially young women. This is caused by the need for more energy and nutrient consumption to meet the body's needs. One strategy to overcome undernourished is to fulfil nutritional intake by providing nutritional supplements as additional popular food, for example cookies. Cookies Moerhi are made white sweet potato flour (Ipomoea batatas L.) and tempeh flour as a subtitute for some wheat flour.Objectives: This study aimed to determine the effect of Cookies Moerhi on body weight and micronutrient intake in undernourished young women.Methods: The research design was quasi-experimental with pre-test and post-test with control group design. The study was conducted in May-June 2024; a sample of 33 people was divided into three treatment groups:1) the control group was given Cookies Control and nutrition education; 2) intervention group 1 was given Cookies Moerhi formula 1 (20% white sweet potato flour, 10% tempeh flour) and nutrition education; 3) intervention group 2 was given Cookies Moerhi formula 2 (10% white sweet potato flour, 20% tempeh flour).Results: The results showed that giving Cookies Moerhi formula 1 and nutrition education for 21 days can increase the average body weight (p = 0.009), energy intake (p = 0.007), protein (p = 0.014), and fat (p = 0.003), while Cookies Moerhi formula 2 can increase the average fat intake (p = 0.033). Cookies Control can increase the average body weight (p = 0.006) and energy intake (p = 0.030).Conclusions: Giving Cookies Moerhi formula 1 and nutrition education showed better results because it can increase body weight, energy intake, protein intake and fat intake in undernourished adolescent girls. Keyword: adolescents; body weight; cookies; macronutrient intake; undernourished